Systemic Thinking as Foundational Competence: Insights from Social Sciences and Humanities Students in Mexican Higher Education. - Vázquez-Parra, José Carlos; Cruz-Sandoval, Marco; Suárez-Brito, Paloma; López-Caudana, Edgar Omar (International Journal of Humanities Education, 2026)
This article analyzes the perceived competencies of first-year students entering social sciences and humanities programs at a technological university in western Mexico, focusing specifically on systemic thinking as a foundational metacompetency. The study examines whether these students possess a competency profile aligned with the demands of their disciplinary training and the broader challenges of humanistic education. Complex thinking was approached as a macrocompetency composed of four subdimensions, with systemic thinking prioritized due to its interdisciplinary relevance and its capacity to foster holistic understanding of interrelated social phenomena. Drawing on a sample of 255 students, the study employed the e-Complexity instrument to assess perceived achievement across disciplines. Statistically significant results indicate that students in social sciences and humanities exhibit higher self-perception in systemic thinking compared to peers in engineering and sciences. Gender-based differences were also observed, with women in these disciplines reporting the highest levels of systemic thinking. These findings underscore the centrality of systemic thinking for future professionals engaged in addressing multifaceted societal issues. The study advocates for integrating systemic thinking into curricular design to enhance students' readiness for complex, interconnected realities. It concludes that this competency is not only crucial within humanistic disciplines but also transferable and essential across broader educational and professional contexts.